'These sorts of people don't do very well': race and allocation of health care resources. Issue 6 (December 1995) - Lowe, M; Kerridge, I H; Mitchell, K R
Abstract : Recent literature has highlighted issues of racial discrimination in medicine. In order to explore the sometimes subtle influence of racial determinants in decisions about resource allocation, we present the case of a 53-year-old Australian Aboriginal woman with end-stage renal failure. The epidemiology of renal failure in the Australian Aboriginal population and amongst other indigenous peoples is discussed. We show that the use of utilitarian outcome criteria for resource allocation may embody subtle racial discrimination where consideration is not given to issues of justice, race, culture and gender. It is only where the processes by which resources are allocated are transparent, clearly defined and based upon consultation with individual patients that issues and justice are likely to be adequately addressed.